Audiophonologopedic Telerehabilitation: Advantages and Disadvantages from User Perspectives - Maria Lauriello; Anna Maria Angelone; Sara Iannotti; Eleonora Nardecchia; Benedetta Scopano; Alessandra Fioretti; Irene Ciancarelli; Alberto Eibenstein (MDPI AG, 2024)
Introduction: Technological advancements and the COVID-19 pandemic have highlighted the importance of digital tools for patient care and rehabilitation. This study explores user perspectives on telerehabilitation, comparing it to traditional methods and identifying criteria for determining its suitability for different patients and clinical conditions. Methods: This study was carried out during the period of May-September 2021. Questionnaires were administered to 48 users in rehabilitation for audiophonologopedic and neurodevelopmental disorders in three rehabilitation centres in central Italy. Results: The user responses predominantly emphasize the benefits of time saving (68.75%) and cost-efficiency (37.5%), specifically regarding time saving due to travel and expenses incurred to go to where the therapy is carried out. The disadvantages include increased distraction (60.42%) in following the instructions remotely and logistic problems (39.58%). Patients with hearing loss were subjected to a larger number of telerehabilitation sessions, positively rating this alternative method. Patients with speech and language delay and autism spectrum disorder (ASD) prefer traditional treatment. Discussion: This study reveals a favourable perception of telerehabilitation as a therapy approach to be regarded as a supplement or temporary option to the irreplaceable face-to-face one. More research, as well as a larger sample sizes, will be useful to increase the significance of the correlations reported in this study.